ANALISIS KINERJA PENYULUH PERTANIAN KABUPATEN BOGOR - Wiwik Yuniarti; Yoyon Haryanto (Jurnal Penyuluhan Pertanian, 2020)
This research aimed to describe the level of performance of agricultural extension workers after participating in the functional extension training programs, and to describe the influence factors of agricultural extension workers performance in Bogor Regency. The populations were the agricultural extension workers graduated from the functional extension training programs and the number of them are 89. The research variables included: independent variables, which consist of four factors that covered characteristics of the agricultural extension workers (X1), training process (X2), supporting factors of agricultural extension (X3), and environmental factors (X4); and dependent variables that covered the competencies (Y1) and the performance of the agricultural extension workers (Y2). Data analysis techniques included descriptive statistics analysis to describe the research data, and path analysis to predict the independent variables towards the dependent variables to determine direct and indirect effects among variables. The results of the research showed that the factor with dominant influence is characteristics of the agricultural extension workers.